Case report: Simultaneous measurement of intracranial pressure and lumbar intrathecal pressure during epidural patch therapy for treating spontaneous intracranial hypotension syndrome. Spontaneous intracranial hypotension or spontaneous intraspinal hypovolume? - Engrand, Nicolas; Salardaine, Quentin; Desilles, Jean-Philippe; Echard, Cécile; Bourdillon, Pierre; Williams, Marc; Baille, Guillaume (Frontiers in Neurology, 2024)
Objectives Spontaneous intracranial hypotension (SIH) is frequently complicated by subacute subdural hematoma (SDH) and more rarely by bilateral thalamic ischemia. Here, we report a case of SIH-related SDH treated with three epidural patches (EPs), with follow-up of the intracranial pressure and lumbar intrathecal pressure. Methods A 46-year-old man presented bilateral thalamic ischemia, then a growing SDH. After failure of urgent surgical evacuation, he underwent three saline EPs, two dynamic myelography examinations and one digital subtraction angiography–phlebography examination. However, because of no dural tear and no obstacle to the venous drainage of the vein of Galen, no therapeutic procedure was available, and the patient died. Results The case exhibited a progressive increase in the transmission of lumbar intrathecal pressure to intracranial pressure during the three EPs. The EPs may have successfully treated the SIH, but the patient did not recover consciousness because of irreversible damage to both thalami. Conclusion Clinicians should be aware of the bilateral thalamic ischemia picture that may be the presenting sign of SIH. Moreover, the key problem in the pathophysiology of SIH seems to be intraspinal and intracranial volumes rather than pressures. Therefore, intracranial hypotension syndrome might actually be an intraspinal hypovolume syndrome.